Caracterização e avaliação de rizobactérias isoladas sob condições de restrição hídrica em plantas de feijão comum - Henrique, Ivanildo Guilherme (2021)
Water stress is one of the main limitations to the productivity of the bean crop, when grown in regions or times subject to periods of drought. In addition to water restriction, high temperatures can affect the persistence and influence the survival of rhizobia cells inoculated in the soil, limiting nodulation and biological nitrogen fixation (BNF). Thus, it becomes necessary to identify bacteria, with symbiotic efficiency, in adverse conditions, mainly of humidity and temperature. Bacteria that have other biochemical abilities that favor plant development, such as the ability to solubilize inorganic phosphates and synthesize plant hormones, such as indolylacetic acid (IAA). In this sense, the objective was to characterize and evaluate bacterial strains native to soils in the municipality of Sinop-MT, isolated under water restriction conditions in bean plants. Initially, these bacteria were phenotypically characterized and had their tolerance to environmental stresses evaluated in vitro. Phosphate solubilization capacity, IAA synthesis, as well as tolerance to high temperatures and acidity were measured. Strains were evaluated for nodulation capacity, symbiotic efficiency, and potential to promote growth in bean plants. In order to evaluate whether the bacterial strains have symbiotic efficiency under water deficit and if the performance of bean plants improves, trials were carried out in a greenhouse. In these assays, strains selected were used based on the results of nodulation and symbiotic efficiency, and on the capacity for phosphate solubilization and IAA production. The results show the ability of some isolates to fix nitrogen, promote the solubilization of calcium phosphate and produce IAA. The ability to synthesize IAA by the isolates provides greater production of dry matter from the aerial part. The isolates respond differently to the rise in temperature. We detected, among the evaluated isolates, potential growth promoters in bean plants, tolerant to environmental stress. The isolates FNE01, FNE04, FNE06 and FNE07 show nodulation and symbiotic efficiency in fixing atmospheric nitrogen in bean plants. The availability of water in the soil interferes with the proper development of bean plants. The increase in water tension in the soil causes an increase in the root: aerial part ratio. Plants subjected to 4 days of water restriction showed a reduction in leaf water content and nodule viability. Isolate FNE04 had the highest accumulation of biomass and FNE06 had the highest percentage of active nodules after a period of water failure of 4 days.